2016
DOI: 10.1098/rsbl.2016.0689
|View full text |Cite
|
Sign up to set email alerts
|

Goffin's cockatoos make the same tool type from different materials

Abstract: Innovative tool manufacture is rare and hard to isolate in animals. We show that an Indonesian generalist parrot, the Goffin's cockatoo, can flexibly and spontaneously transfer the manufacture of stick-type tools across three different materials. Each material required different manipulation patterns, including substrates that required active sculpting for achieving a functional, elongated shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 9 publications
2
39
1
Order By: Relevance
“…Parrots have only recently become the focus of a sustained, global research effort 61 . Behaviour suggestive of more domain-general processes have emerged in both groups from studies examining the ability of non-tool users to solve tool problems 48,49,[62][63][64][65][66] . Our results both support these claims and greatly extend them, in showing that the integration of very different types of information-concerning physical barriers and sampling biases-into statistical inferences is possible in at least the mind of one parrot species.…”
Section: Discussionmentioning
confidence: 99%
“…Parrots have only recently become the focus of a sustained, global research effort 61 . Behaviour suggestive of more domain-general processes have emerged in both groups from studies examining the ability of non-tool users to solve tool problems 48,49,[62][63][64][65][66] . Our results both support these claims and greatly extend them, in showing that the integration of very different types of information-concerning physical barriers and sampling biases-into statistical inferences is possible in at least the mind of one parrot species.…”
Section: Discussionmentioning
confidence: 99%
“…Tool use innovations can be transmitted to naïve individuals by emulation learning and tool-using subjects are thereafter able to independently innovate tool manufacture (Auersperg et al, 2014). The birds respond flexibly, not only when choosing a tool, but also when making different tools from different materials depending on the problem at hand (Auersperg et al, 2016;Laumer et al, 2016Laumer et al, , 2017Habl & Auersperg, 2017;Auersperg et al, in press). It was also shown that they keep their tools safe in between foraging bouts (Auersperg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Almost every time that we can see pieces falling down (89%), there is an object in use, but we do not know if the use of these objects is truly helpful for the bird or just a vain attempt to further open the hole of the coconut. Nevertheless, importantly, intense combinations of objects with food sources as described in this case combined with very fast operant and social learning abilities, flexible extractive foraging and the capacity for tool use in captivity (Auersperg et al, 2012(Auersperg et al, , 2016Auersperg, Laumer, & Bugnyar, 2013;Auersperg, Kacelnik, & von Bayern, 2013) do generally constitute a scenario that could easily prompt the innovation and spread of tool use in a foraging context if the outcome of such a combination did prove advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing field investigations on Tanimbar strongly suggest that they are neither specialized nor species-wide tool users (unpublished data, ongoing field work). Nevertheless, they have shown the capacity for highly flexible tool use and manufacture under laboratory conditions, rivaling the skills of habitually tool-using birds (Auersperg, Szabo, von Bayern, & Kacelnik, 2012;Auersperg et al, 2014;Auersperg, Borasinski, Laumer, & Kacelnik, 2016;Auersperg, Köck, Pledermann, O'Hara, & Huber, 2017). Unlike habitually tool using birds, they do not construct complex nest cups and they lack food caching ancestry, two ecological drivers that have been proposed to have prompted the onset of tool use in birds (e.g., discussed in Kenward, Rutz, Weir, & Kacelnik, 2006: Hansell & Ruxton, 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation